2024
DOI: 10.1186/s12964-023-01411-x
|View full text |Cite
|
Sign up to set email alerts
|

KIT mutations and expression: current knowledge and new insights for overcoming IM resistance in GIST

Shishan Zhou,
Omar Abdihamid,
Fengbo Tan
et al.

Abstract: Gastrointestinal stromal tumor (GIST) is the most common sarcoma located in gastrointestinal tract and derived from the interstitial cell of Cajal (ICC) lineage. Both ICC and GIST cells highly rely on KIT signal pathway. Clinically, about 80-90% of treatment-naive GIST patients harbor primary KIT mutations, and special KIT-targeted TKI, imatinib (IM) showing dramatic efficacy but resistance invariably occur, 90% of them was due to the second resistance mutations emerging within the KIT gene. Although there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 237 publications
0
2
0
Order By: Relevance
“…A meta-analysis shows that neoadjuvant chemotherapy may improve 5 years overall survival, while local excision reduces hospitalization time ( 67 ). Recent studies have shown significant differences between GIST and wild-type (WT) KIT mutations, offering potential therapeutic perspectives and targets for overcoming imatinib resistance ( 69 ). Despite some progress in current therapeutic approaches, the outcome for certain GIST patients remains suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis shows that neoadjuvant chemotherapy may improve 5 years overall survival, while local excision reduces hospitalization time ( 67 ). Recent studies have shown significant differences between GIST and wild-type (WT) KIT mutations, offering potential therapeutic perspectives and targets for overcoming imatinib resistance ( 69 ). Despite some progress in current therapeutic approaches, the outcome for certain GIST patients remains suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the most mutated genes in GIST are the KIT and PDGFRA gene mutations [ 68 ]. Identifying these mutations is vital as there is specific therapy for them [ 69 , 70 ]. A CNN model was proposed by Liang et al (2021) [ 42 ] to identify the KIT and PDGFRA gene mutations based on the histologic images.…”
Section: Mutation Identificationmentioning
confidence: 99%